Segregation texts: Riksdag's open data: Written questions - Språkbanken Text (University of Gothenburg, 2024)
Written questions from members of the Riksdag to the Government and the answer to these

Skriftliga frågor från ledamöterna till regeringen och svaren på dessa
Segregationstexter: Riksdagens öppna data: Skriftliga frågor
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik